Deepak Scored 45->99%ile with Bounce Back Crack Course. You can do it too!

Mark the tick against the correct answer in the following:

Question:

Mark the tick against the correct answer in the following:

The value of $\operatorname{cosec}^{-1}\left(\operatorname{cosec} \frac{4 \pi}{3}\right)$ is

A. $\frac{\pi}{3}$

B. $\frac{-\pi}{3}$

C. $\frac{2 \pi}{3}$

D. none of these

 

Solution:

To Find: The value of $\operatorname{cosec}^{-1}\left(\operatorname{cosec}\left(\frac{4 \pi}{3}\right)\right)$

Now, let $x=\operatorname{cosec}^{-1}\left(\operatorname{cosec}\left(\frac{4 \pi}{3}\right)\right)$

$\Rightarrow \operatorname{cosec} x=\operatorname{cosec}\left(\frac{4 \pi}{3}\right)$

Here range of principle value of cosec is $\left[-\frac{\pi}{2}, \frac{\pi}{2}\right]$

$\Rightarrow \mathrm{x}=\frac{4 \pi}{3} \notin\left[-\frac{\pi}{2}, \frac{\pi}{2}\right]$

Hence for all values of $x$ in range $\left[-\frac{\pi}{2}, \frac{\pi}{2}\right]$, the value of

$\operatorname{cosec}^{-1}\left(\operatorname{cosec}\left(\frac{4 \pi}{3}\right)\right)$ is

$\Rightarrow \operatorname{cosec} x=\operatorname{cosec}\left(\pi+\frac{\pi}{3}\right)\left(\because \operatorname{cosec}\left(\frac{4 \pi}{3}\right)=\operatorname{cosec}\left(\pi+\frac{\pi}{3}\right)\right)$

$\Rightarrow \operatorname{cosec} x=\operatorname{cosec}\left(-\frac{\pi}{3}\right)(\because \operatorname{cosec}(\pi+\theta)=\operatorname{cosec}(-\theta))$

$\Rightarrow x=-\frac{\pi}{3}$

 

Leave a comment

None
Free Study Material